Mengungkap Faktor-Faktor Pendorong Penggunaan Beli Sekarang Bayar Nanti: Bukti dari Investor Generasi Z di Jakarta - Riska Rosdiana; Sik Sumaedi; Winda Widyanty; Febrina Mahliza; Dian Primanita Oktasari (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2026)
The rapid rise of Buy Now Pay Later (BNPL) services has transformed consumer behavior, especially among Generation Z as digital natives. This study investigates the influence of financial literacy, risk perception, interest rate perception, social environment, and religiosity on BNPL usage among Generation Z investors in Jakarta. Using a sample of 200 respondents aged 17 and above, data were analyzed with structural equation modeling–partial least squares (SEM-PLS). The results show that financial literacy, risk perception, and education level do not significantly affect BNPL usage, as financially literate and risk-averse students tend to avoid BNPL altogether. In contrast, interest rate perception significantly influences BNPL usage, where respondents view flexible installment terms as acceptable despite higher costs. These findings extend the Theory of Planned Behavior in the context of fintech adoption and provide insights for fintech firms and regulators to design transparent products, strengthen consumer protection, and enhance financial literacy for responsible BNPL usage.